2022
DOI: 10.3389/fpsyg.2022.844173
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Family Socioeconomic Status and Learning Burnout of College Students: The Mediating Role of Subjective Well-Being and the Moderating Role of Resilience

Abstract: ObjectiveLearning burnout affects the positive development of college students. The present study aimed to investigate the relationship between family socioeconomic status (FSES) and learning burnout, as well as the mediation effect of subjective well-being and the moderation effect of resilience in this relation.MethodsA total of 550 Chinese college students from Yunnan completed a questionnaire measuring the research variables in this study.Results(1) After controlling for participants’ gender and age, FSES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Scholars like Chen et al [13], Wu et al [22], Cheng, [23], Virtanen et al [25], Kinnunen [26] all devote their efforts to investigating the mediating and moderating roles between FSES and school burnout. Their results are consistent: FSES not only directly predict school burnout but also indirectly predict it via mediating or moderating variables such as smoking, boredom, self-control self-concept, family emotional environment or self-efficacy.…”
Section: Mediating and Moderating Variables Between Fses And School B...mentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars like Chen et al [13], Wu et al [22], Cheng, [23], Virtanen et al [25], Kinnunen [26] all devote their efforts to investigating the mediating and moderating roles between FSES and school burnout. Their results are consistent: FSES not only directly predict school burnout but also indirectly predict it via mediating or moderating variables such as smoking, boredom, self-control self-concept, family emotional environment or self-efficacy.…”
Section: Mediating and Moderating Variables Between Fses And School B...mentioning
confidence: 99%
“…From the existing literature, it is obvious that school burnout syndrome is a worldwide phenomenon. Researchers have carried out their surveys of FSES and school burnout in the context of China and Korea [21][22][23][24]; and scholars like Samela, Sanna have expounded their studies in Finland [5,12,16]; and studies conducted among students in UK, USA, Belgium and other European Countries have also been found [3,15]. It seems that FSES can be a factor of school burnout regardless of one's nationality, but the extent varies from countries.…”
Section: Culture Gender Grade and Other Affecting Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as a result of treating psychological problems, psychiatrists are prone to EE, which affects their general WB [ 37 ]. Arrogante and Aparicio-Zaldivar found that high scores for EE predict low levels of WB among intensive care professionals [ 36 ]. Alhadi et al argued that there is a need for the improvement of mental health professionals’ WB, as they are at a high risk of EE [ 71 ].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…To cope with the negative emotions caused by work pressure, there is a call for studies on college teachers’ WB in relation to EE, in the hope of fostering their ability to overcome EE and seek WB. However, existing research on EE and WB has focused on teachers in elementary schools, secondary schools, and high schools [ 36 , 37 ]; however, college teachers face different challenges [ 13 , 14 , 15 ]. Therefore, there is a need for more empirical studies on the effect of EE on college teachers’ WB.…”
Section: Introductionmentioning
confidence: 99%